2005
DOI: 10.1016/j.ultras.2005.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of multiple acoustic wave modes for assessment of long bones: Model study

Abstract: Multiple acoustic wave mode method has been proposed as a new modality in axial bone QUS. The new method is based on measurement of ultrasound velocity at different ratio of wavelength to the bone thickness, and taking into account both bulk and guided waves. It allows assessment of changes in both the material properties related to porosity and mineralization as well as the cortical thickness influenced by resorption from inner layers, which are equally important in diagnostics of osteoporosis and other bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 30 publications
2
33
0
5
Order By: Relevance
“…Initially, this was achieved by the introduction of multiparametric analysis based on multifrequency scanning and followed by the application of advanced data acquisition tools [39], [40]. This renewed approach is based on the measurement of ultrasound velocity at different ratios of wavelength to the bone thickness at various carrier frequencies ranging from 100 kHz to over 1 MHz.…”
Section: Multifrequency Scanning Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, this was achieved by the introduction of multiparametric analysis based on multifrequency scanning and followed by the application of advanced data acquisition tools [39], [40]. This renewed approach is based on the measurement of ultrasound velocity at different ratios of wavelength to the bone thickness at various carrier frequencies ranging from 100 kHz to over 1 MHz.…”
Section: Multifrequency Scanning Technologymentioning
confidence: 99%
“…The technology incorporating guided waves and assessment of topography has been further advanced at Artann Laboratories (West Trenton, NJ) by introducing several innovations: multifrequency data acquisition based on the implementation of broadband transducers run by a programmable waveform generator with stepped switching of frequency; multiparametric data analysis gaining information differentially at low and high frequencies; and axial-stepped scanning along the bone [39]. These principles were implemented in the bone ultrasonic scanner (BUSS) [40] illustrated in Fig.…”
mentioning
confidence: 99%
“…Tatarinov et al. measured the propagation of these waves in long bone and found that the wave velocity in bone had a similar dependence on thickness as the A0 Lamb wave in plates at the frequency of 100 kHz (5) . In a simplified model of the bone cortical region presented as a plane layer, the A0 Lamb wave can be generated at frequencies that correspond to wavelengths that are much greater than the cortical thickness.…”
Section: Introductionmentioning
confidence: 98%
“…Mathematical modeling of absorption and scattering by polymer viscoelastic (VE) materials subjected to acoustical waves is an active field of research in various fields including biomedical ultrasound for drug delivery and the design of layered particles [1], elongated bone samples [2] and micro-vessel [3] characterization to name a few areas. For a mathematical model describing the behavior of an isotropic VE polymer-type material in which the stress varies linearly with strain, a hysteresis-type of absorption has been assumed and validated experimentally [4].…”
Section: Introductionmentioning
confidence: 99%